Application of Organic Coal Fertilizer and Rabbit Farm Waste on Pumelo (Citrus grandis L. Osbeck) Seed Growth - Made Sri Yuliartini; I Gusti Made Arjana; Ida Bagus Komang Mahardika (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2022)
The pumelo population in Bali is declining one is caused of a lack of good-quality seeds. This research was conducted to determine the effectiveness of organic coal fertilizer and rabbit farm waste as organic fertilizers for the growth of pomelo grafting seedlings. The research design used a nested pattern randomized block design with 3 replications. There are two factors, the first factor is the type of fertilizer, which are Coal fertilizers, Rabbit Farm Waste fertilizers, and Cow Manure fertilizers. The second factor is the dose of each type of fertilizer which consists of 3 levels, namely: 10 tons/ha; 20 tons/ha; and 30 tons/ha. The results showed that the effectiveness of the treatment of the type of organic fertilizer and the dose of the type of organic fertilizer had no significant effect on all observed variables. This shows that both coal fertilizer and rabbit manure have almost the same quality as cow manure in influencing the growth of pomelo seedlings. The effectiveness of fertilizers tested on the average shoot length of grafting tends to show the highest yields obtained at the highest dose (30 tons/ha), namely Coal fertilizer which is 28.80 cm, rabbit manure is 31.87 cm, and cow manure obtained is 28.13 cm.